Ultra-sensitive long-range surface plasmon modes in asymmetric double-electrode waveguide - Zhou, Yanyan (2013)
We present a theoretical study on an index-asymmetric double-electrode waveguide structure and identify a long-range surface plasmon polariton (LRSPP) super-mode for index-sensing. We propose to operate the LRSPP by monitoring its cut-off wavelength which promises ultra-sensitivity. The sensitivity is calculated to be 6.5×104 nm per refractive index unit (RIU), which is one order magnitude higher than most plasmonic sensors based on spectral interrogation. Additionally, based on computations from the transfer matrix theory, we present the properties of this LRSPP supermode.